Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1002/cyto.b.20028
|View full text |Cite
|
Sign up to set email alerts
|

Enumeration of antigen‐specific CD8+ T lymphocytes by single‐platform, HLA tetramer‐based flow cytometry: A European multicenter evaluation

Abstract: Background: HLA class I peptide tetramers represent powerful diagnostic tools for detection and monitoring of antigen-specific CD8 ؉ T cells. The impetus for the current multicenter study is the critical need to standardize tetramer flow cytometry if it is to be implemented as a routine diagnostic assay. Hence, the European Working Group on Clinical Cell Analysis set out to develop and evaluate a single-platform tetramer-based method that used cytomegalovirus (CMV) as the antigenic model. Methods: Absolute num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 36 publications
(73 reference statements)
1
17
1
1
Order By: Relevance
“…Considering these favorable characteristics, it was rather unexpected that earlier proficiency panels organized by CIP, CIC and others, reported considerable inter-laboratory variability in detecting rare antigen-specific T cells. Some parameters of cell handling that influence assay performance were identified, including the number of cells per test and whether a dump channel was used [23, 28, 37, 39]. Furthermore, gating strategies and marker settings varied, including cases of incorrect cell-subset gating that may contribute to the variability of the results [23].…”
Section: Discussionmentioning
confidence: 99%
“…Considering these favorable characteristics, it was rather unexpected that earlier proficiency panels organized by CIP, CIC and others, reported considerable inter-laboratory variability in detecting rare antigen-specific T cells. Some parameters of cell handling that influence assay performance were identified, including the number of cells per test and whether a dump channel was used [23, 28, 37, 39]. Furthermore, gating strategies and marker settings varied, including cases of incorrect cell-subset gating that may contribute to the variability of the results [23].…”
Section: Discussionmentioning
confidence: 99%
“…While pp65 495-503 is a dominant CMV T cell epitope and is widely used to assess anti-CMV T cell responsiveness (Wills et al 1996;Heijnen et al 2004;Brooimans et al 2008;Pita-Lopez et al 2009), additional CMV-specific epitopes within the CD8 + T cell pool were not evaluated in this study. In addition, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, standardization approaches should be omitted during the initial development but are absolutely required when assays have become Wrmly established. In recent years, several activities aiming at the harmonization of techniques used to monitor the presence of antigen-speciWc T-cells have been initiated for ELISPOT [28][29][30][31], tetramer staining [32] and ICS [33][34][35][36]. While these studies showed the feasibility, general applicability and the diversity of performance among participants, they were not designed to either systematically investigate the inXuence of distinct protocol variables nor to test whether changes to these parameters can lead to a global improvement of the group.…”
Section: Discussionmentioning
confidence: 99%